Assessing the impacts of Saskatchewan's minimum alcohol pricing regulations on alcohol‐related crime. (7th November 2016) - Stockwell, Tim; Zhao, Jinhui; Sherk, Adam; Callaghan, Russell C.; Macdonald, Scott; Gatley, Jodi
Abstract: Introduction: Saskatchewan's introduction in April 2010 of minimum prices graded by alcohol strength led to an average minimum price increase of 9.1% per Canadian standard drink (=13.45 g ethanol). This increase was shown to be associated with reduced consumption and switching to lower alcohol content beverages. Police also informally reported marked reductions in night‐time alcohol‐related crime. Objectives: This study aims to assess the impacts of changes to Saskatchewan's minimum alcohol‐pricing regulations between 2008 and 2012 on selected crime events often related to alcohol use. Methods: Data were obtained from Canada's Uniform Crime Reporting Survey. Auto‐regressive integrated moving average time series models were used to test immediate and lagged associations between minimum price increases and rates of night‐time and police identified alcohol‐related crimes. Controls were included for simultaneous crime rates in the neighbouring province of Alberta, economic variables, linear trend, seasonality and autoregressive and/or moving‐average effects. Results: The introduction of increased minimum‐alcohol prices was associated with an abrupt decrease in night‐time alcohol‐related traffic offences for men (−8.0%, P < 0.001), but not women. No significant immediate changes were observed for non‐alcohol‐related driving offences, disorderly conduct or violence. Significant monthly lagged effects were observed for violent offences (−19.7% at month 4 to −18.2% at month 6), which broadly corresponded to lagged effects in on‐premise alcohol sales. Discussion: Increased minimum alcohol prices may contribute to reductions in alcohol‐related traffic‐related and violent crimes perpetrated by men. Observed lagged effects for violent incidents may be due to a delay in bars passing on increased prices to their customers, perhaps because of inventory stockpiling. [Stockwell T, Zhao J, Sherk A, Callaghan RC, Macdonald S, Gatley J. Assessing the impacts of Saskatchewan's minimum alcohol pricing regulations on alcohol‐related crime. Drug Alcohol Rev 2017;36:492–501]